501POncogenic mutations at the dimer interface of EGFR lead to formation of covalent homo-dimers and allosteric activation of the kinase domain: A mechanism which alters the selectivity profile of oncogenic EGFR. (1st October 2019) - Buck, E; O'Connor, M; Flohr, A; Iacone, R; Nicolaides, T; Zhang, J; Mayweg, A V; Epstein, D M
Abstract: Background: Mutation of either the intracellular catalytic domain or the extracellular domain of the receptor for epidermal growth factor (EGFR) drives oncogenicity. Extracellular domain EGFR mutations are highly expressed in patients with glioblastoma. Despite clinical success with targeting EGFR catalytic site mutants, no drugs have proven effective in glioblastoma patients expressing extracellular EGFR mutations. Methods: Herein, we define the molecular mechanism for oncogenic activation of families of extracellular EGFR mutations and reveal how this mechanism renders current generation small molecule ATP-site inhibitors ineffective. We define these types of lesions as allosteric oncogenic mutations. Results: We demonstrate that a group of the most commonly expressed extracellular domain EGFR mutants expressed in glioblastomas is activated by disulfide-bond mediated covalent homodimerization, collectively referred to as locked dimerization (LoDi-EGFR oncogenes). Strikingly, current generation small molecules binding to the active kinase conformation potently inhibit catalytic site mutants, but induce covalent dimerization and activate LoDi-EGFR receptors, manifesting in paradoxical acceleration of proliferation. Herein we describe the discovery of novel ATP competitive small molecules that potently (<50nM) inhibit the family of LoDi-EGFR oncogenes expressed in GBM, and importantly, achieve selectivity versus WT-EGFR of greater than 10-fold. Conclusions: These data demonstrate how the locked-dimer mechanism of EGFR oncogenesis has profound impact on the activity of small molecules acting at the distal catalytic site, providing further evidence for "inside-out" allosteric signaling in EGFR. This provides a mechanistic understanding for the failure of current generation EGFR inhibitors to effectively treat LoDi-EGFR mutants in GBM and sets guidelines for the discovery and development of novel selective LoDi-EGFR inhibitors. Legal entity responsible for the study: Black Diamond Therapeutics. Funding: Black Diamond Therapeutics. Disclosure: E. Buck: Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment: Black Diamond Therapeutics. M. O'Connor: Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment: Black Diamond Therapeutics. A. Flohr: Leadership role, Shareholder / Stockholder / Stock options: Black Diamond Therapeutics. R. Iacone: Leadership role, Shareholder / Stockholder / Stock options: Black Diamond Therapeutics. A.V. Mayweg: Leadership role, Shareholder / Stockholder / Stock options, Officer / Board of Directors: Black Diamond Therapeutics. D.M. Epstein: Leadership role, Shareholder / Stockholder / Stock options, Officer / Board of Directors: Black Diamond Therapeutics. All other authors have declared no conflicts of interest.